Glyco-nanoparticles with aggregation-induced emission for detection of phenols. (5th December 2022) - Li, Die; Yang, Tao; Luo, Xinzhao; Zhang, Qiang
Graphical abstract: Highlights: Glycopolymers and tetraphenylethylene derivatives self-assemble into nanoparticles. Fluorescence intensity of nanoparticles increases with glycopolymer concentration. Phenols containing vicinal diols can destroy boronate esters bonds between nanoparticles. The glyco-nanoparticles can be used for specific detection of phenols. Abstract: The glucose-containing polymer (PGlu) and boronic acid functionalized tetraphenylethylene (TPEDB) self-assembled into glyco-nanoparticles linked by boronate esters. Such nanoparticles have shown a typical aggregation-induced emission (AIE) effect. Phenols containing vicinal diols could break the reversible boronate esters connecting nanoparticles due to their higher affinity for boronic acid groups than that of saccharides. Therefore, these glyco-nanoparticles with AIE activity could be used as a selective and sensitive fluorescent probe for phenols with vicinal diols.